First record of a freshwater cave sponge (Porifera, unknown gen. and sp.) in a cave inhabited by Astyanax cavefish in the Sierra de El Abra, San Luis Potosí, Mexico - Legendre, L.; Espinasa, L.; Lacaille-Múzquiz, J.-L.; Alaniz-Garfía, G.; Ornelas-García, P.; Rétaux, S. (Subterranean Biology, 2023)
The karstic cave, la Cueva de Los Sabinos, located in the Sierra de El Abra in the state of San Luis Potosí, Mexico, is mostly known for hosting a population of blind, depigmented Astyanax mexicanus cavefish. Herein, we report the discovery of a non-pigmented sponge (Porifera) in the final sump of this cave. No genus or species name could be attributed because we did not collect any specimen. Up to now, the sponge distribution seems restricted to a single pool in la Cueva de Los Sabinos, but further careful exploration of other pools of the cave as well as closely related cavities is warranted. To our knowledge, this observation constitutes the fourth report of a freshwater, white, cave-adapted sponge in the world and the first for Mexico and North America. It is also the eleventh troglobite species encountered in Los Sabinos. Our discovery confirms the exceptionally rich biodiversity of this cave ecosystem.